Study on a Heuristic Wheelset Structure without Rail Corrugation on Sharply Curved Tracks. (13th August 2021) - Mei, G. M.; Chen, G. X.; Yan, S.; Chen, R. X.
Abstract : Rail corrugation on low rails of sharp railway curves is still a difficult problem to solve worldwide. Nearly all low rails of the sharp railway curves incur rail corrugation. In the present study, an active method to remedy rail corrugation was studied. From the viewpoint of the frictional self-excited oscillation of a wheelset-track system causing rail corrugation, the effect of wheelset structures on rail corrugation was studied. Three frictional self-excited oscillation models of wheelset-track systems with different wheelset structures were established, which include a heuristic wheelset structure and two being used in the railway industry. The incidence trends of the self-excited oscillations of these three wheelset-track systems were studied. It was found that the wheelset structure has an important effect on rail corrugation, and that the heuristic wheelset structure can restrain or get rid of rail corrugation. With the parameter sensitivity analysis, it was found that when the friction coefficient between the wheel and rail, rail gauge, rail cant, and sleeper span changes to some extent, the heuristic wheelset structure is robust enough to prevent rail corrugation. The proposed heuristic wheelset structure can be used as a potential solution to rail corrugation on sharply curved tracks.